What drives China's economy : economic, socio-political, historical and cultural factors - Ma, Qing-Ping (London : Routledge, 2020)
"The spectacular economic growth experienced by China since 1978 has often been hailed as "the China Miracle". Many economists have tried to understand the forces behind China's phenomenal growth and the explanations can be divided into two broad schools of economic thought - one school of thought which includes Nobel Laureate Paul Krugman explains that market mechanism and deregulation led to China's success, while the other school of thought which include Justin Yifu Lin, the former Chief Economist and Senior Vice-President of the World Bank, explains that China's growth miracle is a unique model to itself defined by the Chinese government's prominent role. The Chinese government has been responsible in identifying and investing in industries that have contributed to economic growth. Some economists in the latter school even claim that "the China Miracle" cannot be explained by mainstream economics. This book examines both schools of thought and attempts to provide a synthesis of the two schools to explain "the China Miracle". It looks at Solow-Swan growth model, Harrod-Domar model and Transaction Cost Theory. It provides insights into whether and how China can sustain its growth and how developing countries may replicate China's success"--
Includes bibliographical references and index.
Keywords: Monetary policy -- China; Investments -- China; Economic development -- Government policy -- China; China -- Economic policy -- 21st century